The indirect jurisdiction of the 2019 Hague Convention on recognition and enforcement of foreign judgments in civil or commercial matters – Is the “heart” of the Convention in the right place? - Rumenov, Ilija (Centre for SEELS, 2021)
The new 2019 Hague Convention on recognition and enforcement of foreign judgments in civil or commercial matters (2019 Hague Convention) represents one of the most awaited international agreements in the legal field of private international law. The final result is far from the initial idea of “dual convention” that will cover both recognition and enforcement of foreign judgments and contain direct jurisdictional rules in civil or commercial matters. It has taken almost 30 years to reach the conclusion that full effectuation of this idea is unreachable in single instrument. However, fragmented parts of this idea have been instrumented in the Hague Conference on Private International Law (HCCH) and materialized as 2005 Hague Convention on Choice of Court Agreements and the most recently with the 2019 Hague Convention. This newest addition to the HCCH discarded the idea regarding the direct jurisdictional rules and opted to implement the indirect jurisdictional rules. The system created by the 2019 Hague Convention is rather very simple: if the judgment regarding civil or commercial matters is rendered in a country which satisfies the indirect jurisdictional filters provided in Article 5 and if the grounds for refusal of recognition in Article 7 are not met, then the judgment can be recognized and enforced in a requested country. However, foreign judgments can be recognized and enforced under national law or other international convention, but with consideration to the exclusive bases given in Article 6. In such way, the indirect jurisdictional rules are the linking point between the country of origin and the country of recognition. This article will analyze the indirect jurisdictional rules in the 2019 Hague Convention and will provide for the compatibility of its effectuation in Republic of North Macedonia (N. Macedonia) in context of the new national Private International Law Act.
Winning paper
Keywords: civil or commercial matters; Hague Convention on Recognition and Enforcement of Foreign Judgments; indirect jurisdiction; recognition and enforcement; Private International Law Act of Republic of North Macedonia.